NEW OSTRACODES FROM THE CRETACEOUS AND PALEOGENE BOUNDARY SEDIMENTS IN SOUTHWESTERN CRIMEA - Savelieva Yu.N. (My University, 2001)
Seven new species of Ostracodes are described in six genera. Representatives of the genus Parapokornyella are recorded for the first time in southwestern Crimea, from the Cretaceous/Paleogene boundary beds.
Keywords: Paleogene; Cretaceous; Ostracodes; Crimea; Мезозой::Меловая; Cenozoic::Paleogene; Mesozoic::Cretaceous; Кайнозой::Палеоген